2020
DOI: 10.1021/acssuschemeng.0c02107
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Robust Bacillus amyloliquefaciens Cell Factory for Efficient Poly(γ-glutamic acid) Production from Jerusalem Artichoke

Abstract: Bacillus amyloliquefaciens NB, a glutamate-independent poly-γ-glutamic acid (γ-PGA)-producing strain, can directly utilize inulin-containing sustainable materials. However, low γ-PGA yield and lack of efficient genetic engineering approaches have hindered the industrial use of this strain. Here, we used the CRISPR-Cas9n technique to engineer B. amyloliquefaciens to enhance γ-PGA production. We engineered three modules involved in inulin hydrolysis, reducing sugars metabolism, and γ-PGA synthesis in B. amyloliq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In an earlier study, we found that B. amyloliquefaciens NB can efficiently use inulin to synthesize PGA and has a highly-efficient tricarboxylic acid cycle metabolic flux and glutamate synthesis ability ( Qiu et al, 2020a ; Sha et al, 2020b ). Therefore, we speculate that this strain may be optimal for synthesizing glutamate derivatives ( L -ornithine).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, we found that B. amyloliquefaciens NB can efficiently use inulin to synthesize PGA and has a highly-efficient tricarboxylic acid cycle metabolic flux and glutamate synthesis ability ( Qiu et al, 2020a ; Sha et al, 2020b ). Therefore, we speculate that this strain may be optimal for synthesizing glutamate derivatives ( L -ornithine).…”
Section: Resultsmentioning
confidence: 99%
“…The gene knockout method refers to previous research reports ( Qiu et al, 2020b ). To knock out argF , upstream and downstream fragments of argF (Gene ID: 56457344) were amplified from B. amyloliquefaciens genome (NC_017190.1) with primer pairs argFL-F/R and argFR-F/R, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with traditional homologous recombination, CRISPR/Cas9 system gene editing requires shorter time and higher efficiency, and has been widely used in various animals, plants and microorganisms [ 38 40 ]. The CRISPR/Cas9 system in B. amyloliquefaciens was not reported for the first time until 2020 [ 19 ]. However, DSBs in the genome caused by Cas9 are often fatal to bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR-based genetic tools developed by other species and strains from the genus Bacillus can be adapted to B. amyloliquefaciens theoretically; however, it needs to be further verified through experiments due to the distinctions between different species. Qiu et al [ 19 ] reported for the first time that a dual plasmid CRISPR/Cas9n system could achieve the disruption of the B. amyloliquefaciens NB gene by integrating the Cas9n protein and sgRNA into two different vectors [ 19 ]. Zhao et al [ 20 ] further fused the nuclease-deficient mutant dCas9 of Cas9 with the ω subunit of RNA polymerase achieved gene transcription regulation in B. amyloliquefaciens 205 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria, archaea, and eukaryotes are all γ-PGA producers, but Bacillus species are the natural, dominant, and safely produced strains [ 7 , 8 , 14 , 15 , 16 ]. Commonly, the production strains are divided into glutamic acid-dependent and glutamic acid-independent strains according to whether there is a need to add glutamate acids externally [ 17 ]. Glutamic acid dependent strains are regarded as the better producers, as adding glutamic acids can significantly increase the yield [ 1 , 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%